2008
DOI: 10.1007/s10719-007-9091-7
|View full text |Cite
|
Sign up to set email alerts
|

Glycosphingolipids in vascular endothelial cells: relationship of heterogeneity in Gb3Cer/CD77 receptor expression with differential Shiga toxin 1 cytotoxicity

Abstract: Shiga toxin (Stx) 1 binds to the glycosphingolipid (GSL) globotriaosylceramide (Gb3Cer/CD77) and injures human endothelial cells. In order to gain insight into Stx1-induced cellular impairment, we analysed in detail the molecular heterogeneity of Stx1 receptors in two endothelial cell lines differing in their Stx1-sensitivity. We observed a moderate sensitivity to Stx1 of human brain microvascular endothelial cells (HBMECs, CD(50) > 200 ng/ml), but a considerably higher mortality rate in cultures of EA.hy 926 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 75 publications
5
48
0
Order By: Relevance
“…1B , lane c), which is in agreement with the results of the orcinol stain ( Fig. 1C ) and previous investigations ( 52 ). the steps.…”
Section: Detection Of Stx Receptors In Neutral Gsl Fractions Of Totalsupporting
confidence: 92%
See 2 more Smart Citations
“…1B , lane c), which is in agreement with the results of the orcinol stain ( Fig. 1C ) and previous investigations ( 52 ). the steps.…”
Section: Detection Of Stx Receptors In Neutral Gsl Fractions Of Totalsupporting
confidence: 92%
“…Lipid raft association of GSLs has been described so far in different cell types, such as intestinal ( 45,50 ), HeLa, and Vero cells (47)(48)(49)46 ), whereas the membrane localization of GSLs of human endothelial cells has so far not been analyzed in detail and remains largely unknown. To this day, the structural characterization of the different lipoforms of Stx GSL receptors of the macrovascular HUVEC-derived EA.hy 926 cell line and human brain microvascular endothelial cells (HBMECs) has been reported by us ( 52 ), indicating that HBMECs express both Gb3Cer and Gb4Cer, whereas EA.hy 926 cells were found to synthesize Gb3Cer but not elongated Gb4Cer. luted 1:500 in PBS with 1% BSA and 0.3% Triton X-100.…”
Section: Lipid Extraction and Isolation Of Neutral Gsls From Endothelmentioning
confidence: 91%
See 1 more Smart Citation
“…It has been shown that the carbohydrate-binding pentameric B-subunit of E. coli verotoxin causes apoptosis in susceptible endothelial cells, such as the Eahy.926 hybridoma cell line, upon binding to the GbO3 glycolipid receptor (64,65), which makes the interaction of GbO3 with endogenous and exogenous ligands a potential target for therapies. The availability of the SadP with its distinct and well characterized Gal␣1-4Gal binding specificity could be a useful tool in studies aiming at these goals.…”
Section: Discussionmentioning
confidence: 99%
“…Fluorochrome-labeled antibodies and DAPI-stained nuclei were evaluated under a fluorescence microscope (Axioskop; Zeiss), original magnification Â40 (objective lense Plan-Neofluar, numerical aperture 0.75), following published protocols (26). To confirm the lipid nature of the positive staining with anti-ganglioside antibodies, lipids were extracted from air-dried sections with methanol and chloroform/methanol (1:1, v/v) for 10 min each and stained by the same procedure as described above.…”
Section: Discussionmentioning
confidence: 99%